GeO2 Modified High-Concentration Er3+/Yb3+ Co-Doped Phosphate Glasses for 1.5 μm High Gain Laser. (10th November 2021) - Zhao, Zigang; Sun, Yingxin; Wang, Lisha; Zhao, Kun; Xin, Fengxin; Li, Chao; Wang, Yong; Zhang, Bingtao
Abstract : The GeO2 modified high-concentration Er 3+ /Yb 3+ co-doped phosphate glasses with composition 64P2 O5 –2ZnO–13BaCO3 –13K2 CO3 –8Al2 O3 –0.5Er2 O3 –12Yb2 O3 – x GeO2 mol% (PEYG, x = 0, 2.5, 5, 7.5, and 10) were successfully prepared by the melt-quenching method. The structure and spectroscopic properties were revealed by analyzing refractive index, expansion coefficient, glass transition temperature, absorption and emission spectra, and laser properties. We studied the relationship between GeO2 doping content and spectroscopic properties, finding that GeO2 could enhance 1535 nm emission of the PEYG glasses. The PEYG modified with 5 mol% GeO2 showed the best spectroscopic properties. The study provided a good guidance for the design of high gain laser glasses and fibers.